Primary headship in a time of systematic change - Portin, B; Portin, Bradley (1995)
The primary headship in England and Wales is in a time of fundamental change and increasing expectations. The influences of recent education acts, and forces, such as choice, parent and governor participation, and increasing LMS responsibility have contributed to a changing headship context. The relative paucity of research which develops a qualitative understanding of primary headteacher perspectives lends an imperative to this qualitative study. A number of central research questions are posed to explore headteacher conceptions of leadership, the influential forces which shape those conceptions, and the context of primary school development. Particular attention is paid to the influence of reflective practice and critical theory as a contribution to professional development. The literature review examines the historic and thematic development of 20th century leadership and management theory. Particular emphasis is placed on what has been termed 'transformational leadership' and the influence of 'reflective practice' in professional development. A case is made for substantive differences between leadership and management, with leadership forming the central core of the study. The data sources were case studies of three perceived 'effective' Oxfordshire primary headteachers; the headteachers represented an opportunity sample of large, multiplestaff primary schools. Semi-structured interviews represented the primary data source, however a breadth of methods were used to form a 'thick' description of the headteacher and school ethos. The repertory grid technique was utilised to illuminate the central constructs which guided the headteachers' conceptions of leadership. Findings from the study are grouped in three areas. The findings suggest headteacher conceptions of leadership were largely idiosyncratic and person-oriented. In addition, a mixed nominal understanding of the terms 'leader' and 'manager' was expressed by the participants. It was found that the headteacher's conception of leadership were influenced by the transitional nature of the headship role. Greater responsibility for LMS, and other governmental forces were indicated as strongly shaping factors. Findings point to the espousal of a number of transformational views, and all headteachers used language of reflective practice to describe a number of the professional development goals of the school. A sense of 'critical' reflection was also present, especially as schools prepared for inspection. The study concludes by discussing the implications for leadership theory and the suggestions for further research in area of headteacher development and evolving conceptions of leadership.